2019
DOI: 10.1002/jmri.26547
|View full text |Cite
|
Sign up to set email alerts
|

MRI breast screening revisited

Abstract: Contrast‐enhanced breast MRI is a standard evidence‐based component of supplemental screening in conjunction with mammography for higher‐risk populations because of its high sensitivity for detecting breast cancer; the use of breast MRI for screening in high‐risk populations is recommended in multiple national and international guidelines. The current MRI exam, however, is expensive relative to other screening technologies such as mammography, and relatively more time‐intensive. Recent investigations have focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 47 publications
1
19
0
1
Order By: Relevance
“…This advantage of CE-BMRI over XRM in detecting malignant breast lesions is in line with findings of other groups, although the clinical trial settings are not always exactly comparable with respect to study population (patients with elevated breast cancer risk (38,39), dense breasts, proven breast cancer (40)) and imaging purpose (screening (39,41), preoperative staging (40), recurrence detection).…”
Section: Discussionsupporting
confidence: 79%
“…This advantage of CE-BMRI over XRM in detecting malignant breast lesions is in line with findings of other groups, although the clinical trial settings are not always exactly comparable with respect to study population (patients with elevated breast cancer risk (38,39), dense breasts, proven breast cancer (40)) and imaging purpose (screening (39,41), preoperative staging (40), recurrence detection).…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies 3,4 found that increased spatial resolution significantly improves diagnostic confidence and accuracy on breast DCE MRI. However, this improvement occurs at the expense of temporal resolution.…”
Section: Discussionmentioning
confidence: 96%
“…Then the intensity of the cropped images was normalized to [0, 1] with min-max normalization. The final preprocessed image dimension was 320 × 128 × 83, with voxel size 0.9 × 0.9 × 1.5 mm 3 .…”
Section: Data Preprocessingmentioning
confidence: 99%
See 2 more Smart Citations